1970
DOI: 10.1159/000155304
|View full text |Cite
|
Sign up to set email alerts
|

The Baboon (Papio ursinus) Heart (Coronary Blood Supply, Muscle Function and Metabolism)

Abstract: The sub-human primate baboon (Papio ursinus) was subjected to cardiac catheterisation studies and pathologic injection techniques with a view to establishing baseline values pertaining to coronary artery morphology, coronary blood flow and myocardial energetics and metabolism. The similarities to the human situation (and minor differences) are considered in the light of possible extrapolation to clinical conditions in contemplated future experimental studies of myocardial physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1971
1971
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The baboon notably has been used as a research model in the areas of vaccine production, organ transplant, and drug trials [4,2]. Brink et al [3] observed that the hemodynamics, coronary blood flow, work performance, and myocardial contractility indices of the baboon did not differ signifi-cantly from those of man. They suggested possible extrapolation of these similarities in experimental studies of myocardial physiology.…”
Section: Introductionmentioning
confidence: 99%
“…The baboon notably has been used as a research model in the areas of vaccine production, organ transplant, and drug trials [4,2]. Brink et al [3] observed that the hemodynamics, coronary blood flow, work performance, and myocardial contractility indices of the baboon did not differ signifi-cantly from those of man. They suggested possible extrapolation of these similarities in experimental studies of myocardial physiology.…”
Section: Introductionmentioning
confidence: 99%
“…They usually either state the predominance of the left coronary artery in the blood supply of the myocar dium [De Waart et al, 1936;Lineback, 1961;Colborn, 1966;H itchcok, 1969] or give detailed anatomic description of each coronary vessel branch without an attempt to give a classification distinguishing between types of blood supply [Abramson and Eisenberg, 1935;C hase, 1938], An attempt to classify myocardial blood supply into 3 types of coronary vessel branching was made by Sokolov [1968], However, it was based on a very small quantity of monkeys. Brink et al [1970] investigated coronary arteries in Papio ursinus and de termined 3 variants of myocardial blood supply (left, right, middle), with the predominance of the left type.…”
mentioning
confidence: 99%